2017
DOI: 10.18203/2349-3933.ijam20173254
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic evaluation of therapeutic response to intralesional triamcinolone acetonide in the treatment of Alopecia areata

Abstract: Background: Alopecia areata is a common auto-immune condition, characterized by circumscribed, patches of hair loss usually of the scalp. There are various treatment modalities available but no treatment is fully curative or preventive. Also, alopecia areata can have devastating effects on the patient’s quality of life and self-esteem. The aim of this study was to determine dermoscopy findings of alopecia areata that could be used as a clinical indicator of disease and also to evaluate the efficacy of intrales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
8
2
0
Order By: Relevance
“…There was a significant improvement in all dermoscopic findings of AA observed from the first session and become more significant at the end of the study. This agrees with the study of Srivastava et al (21) and Ganjoo and Thappa (1) who demonstrated early response to intralesional corticosteroid by dermoscopy, where 67% of the patches showed maximum dermoscopic change by 8 weeks and 91% of the patches showed maximum dermoscopic change by 12 weeks.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was a significant improvement in all dermoscopic findings of AA observed from the first session and become more significant at the end of the study. This agrees with the study of Srivastava et al (21) and Ganjoo and Thappa (1) who demonstrated early response to intralesional corticosteroid by dermoscopy, where 67% of the patches showed maximum dermoscopic change by 8 weeks and 91% of the patches showed maximum dermoscopic change by 12 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, there was statistically significant clinico-dermoscopic relation between hair regrowth and dermoscopic findings at the end of the study, where hair regrowth was more in cases with negative dermoscopic findings of AA as in the study of Srivastava et al (21) who reported significant clinico-dermoscopic relation between regrowth scale and dermoscopic findings reduction.…”
Section: Discussionsupporting
confidence: 69%
“…This is in contrast to other studies showing cumulative effect of TrA with passage of time like Ganjoo et al, 14 who achieved RGS of 4 within 24 weeks of initiating therapy in 95% of patients. A similar effect was also observed in Srivastava et al 16 with a progressive increase of RGS of 4 from 9% of patients at fourth month, to 40% at fifth month and 60% at sixth which reported no substantial side effects of TrA. They reported telangiectasia in 7.5% of cases and 4.6% had atrophy.…”
Section: Re Sultssupporting
confidence: 83%
“…Side effects involved hyperpigmentation in nine patients, erythema in two patients, and erosions in one patient in MTX group, hypopigmentation in two patients, erythema in one patient, and atrophy in one patient in TrA group. Our study suggests that the use of intralesional MTX for AA in adults is safe and sparing the possible systemic adverse effects of MTX use.Similar results were observed in the study of Srivastava et al,16…”
supporting
confidence: 92%
“…Choosing the proper treatment for alopecia areata relies on considering the age of the patient as well as the extent of the disease 12 . Intralesional corticosteroid (ILCs) injection is a good option among adults, 13 and the efficacy is even better within the pediatric group 14 …”
Section: Discussionmentioning
confidence: 99%